Adherence to the Chinese Food Pagoda in the High-Risk Population of Non-communicable Diseases Aged 35–59 in Central China - Jiang, Qingqing; You, Qiqi; Lou, Yiling; Wang, Shiqi; Cao, Shiyi (Frontiers in Nutrition, 2022)
Objectives A healthy dietary habit is essential for preventing non-communicable diseases (NCDs). We aimed to assess the adherence to the Chinese Food Pagoda (CFP) proposed in the Chinese Dietary Guidelines 2016 in the high-risk population of NCDs in central China. Methods A cross-sectional study was conducted in two large enterprises (totally 3,016 employees) from October to December 2019 in Hubei Province (central China). The high-risk population of NCDs was identified by physical examination, laboratory test and face-to-face questionnaire survey according to the National Norms for Prevention and Control of Non-communicable Diseases issued by the Chinese government. We assessed the deviation of real diet from the CFP recommended diet in the high-risk population of NCDs. Results A total of 821 participants aged 35-59 years old with at least one high-risk factor of NCDs were enrolled in our study. Of them, 53.8% were daily smokers, 49.6% had elevated blood cholesterol, 31.4% were centrally obese, 23.3% had high normal blood pressure, and 3.5% had impaired fasting glucose. Significant disparity was detected in the high-risk population of NCDs between real food consumption and the CFP’s recommendation (P < 0.05), such as the deficient intake of nuts and milk and dairy products, and the over-consumption of cereals, meat and poultry, oil, and salt. Participants with impaired fasting glucose had the highest intake of cereals and vegetables on average. Participants with central obesity were more likely to consume meat and poultry (P < 0.05). The lowest average intake of eggs and the highest average intake of milk and dairy products were found in participants with high blood cholesterol (P < 0.05). The daily smokers were more likely to consume beans and nuts (P < 0.05). The lowest average intake of fruits and the highest average intake of tubers were found in participants with high normal blood pressure (P < 0.05). Conclusion Adherence to CFP in the high-risk population of NCDs appeared to be challenging. It is necessary to adopt dietary education campaign focusing on the high-risk population of NCDs to prevent or delay the occurrence of NCDs.